Selection of Tree Species for Energy Plantation in Arid, Semi-arid Area. II. Effect of Fertilizers and Gibberellic Acid - Thaker, Vrinda S.; Singh, Y. D. (Indian Forester, 1999)
Three tree species, Acacia nilotica, Prosopis juliflora and Leucaena leucocephala were treated with different doses of fertilizers and plant growth hormone, gibberellic acid. Growth in terms of fresh weight and dry weight of different plant parts was compared with untreated plants and their role in preparation of better nursery stock is discussed.